SELECTION OF FILMPROOFERS IN MICROCAPSULATION OF VINPOCETIN - Yu. A. Polkovnikova; A. A. Glushko (Фармация и фармакология (Пятигорск), 2018)
Introduction. The scientific and practical interest in the problem of microencapsulation remains high, as evidenced by the extensive literature on this subject. The choice of a film former as a carrier of the active substance in microencapsulation is determined by its required release rate of the latter, which depends largely on the physical properties of the latter. Biodegradable polymers, sodium alginate and gelatin, are often used as a coating. The aim of the research is a comparative analysis of the thermodynamic characteristics of the release of vinpocetine from microcapsules containing gelatin, sodium alginate as a shell, into water and ethanol. Materials and methods. For calculating the thermodynamic characteristics of the release of vinpocetine from polymers, the conformation of the “polymer-vinpocetine” system after thermodynamic equilibration by the molecular dynamics method in the Bioevrica program was the initial state. Results and discussion. The release of vinpocetine from sodium alginate to water with pH = 2 is an energetically beneficial process, and is accompanied by an increase in entropy, which indicates a higher thermodynamic probability of the final state (vinpocetine in solution). The release of vinpocetine from gelatin into water at pH = 2 is an energetically favorable process, as well as accompanied by an increase in entropy, which indicates a higher thermodynamic probability of the final state (vinpocetine in solution). The release of vinpocetine from sodium alginate to ethanol is energetically less favorable than its release to water. The release of vinpocetine from gelatin to ethanol is energetically less favorable than its release into water. Conclusion. A comparative analysis of the results of the quantum-chemical calculation of the thermodynamic characteristics of the release of vinpocetine from sodium alginate and gelatin makes it possible to conclude that vinpocetine has more affinity for sodium alginate in various environments. As a consequence, there may be a higher degree of vinpocetine release into a solution of HCl 0.01 M and an ethanol from gelatin compared to sodium alginate.